ALTERNATIVE MANAGEMENT OF DECOMPRESSION ILLNESS IN BREATH-HOLDING DIVERS USING NPPV - Priyanka Ganesa Utami; Eka Musridharta; Mursyid Bustami; Ita Muharram Sari; Sardiana Salam (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Decompression illness (DI) is a syndrome caused by the formation of gas bubbles during rapid decompression. DI can manifest with neurological manifestations. Divers are at risk of developing DI even in shallow water. Case: A 25-year-old woman lost consciousness after a training dive. She lost consciousness shortly after surfacing, having previously dived to a depth of four meters. She vomited once and denied seizures. This was her third training dive; the second occurred two days prior, and the first ten days prior. The patient was in good health and had no history of heart or lung problems. A non-contrast head CT scan and MRI revealed ischemic lesions in the bilateral thalamus and cerebellum. Chest X-ray (CXR), transthoracic echocardiography (TTE), echocardiography, and bubble contrast scans showed no abnormalities. The patient was treated with 100% oxygen via non-invasive positive pressure ventilation (NPPV – CPAP mode) and showed improvement in her neurological deficits after 10 days. Discussion: DI is associated with vascular or extravascular bubbles that form as a result of rapid decompression. Pure oxygen inhalation using HBOT is the main therapy for DI. But, in the absence of HBOT, NPPV can be considered for its effectiveness to achieve a mean arterial pO2 concentration above 500 mm Hg. Conclusion: Recognizing the signs and symptoms of DI is important because they are nonspecific. Oxygen: 100% oxygen should be administered to those suspected of having DI.